Severely Displased Supracondylar Fracture in Children: Conservative Versus Surgical Treatment - Khudair , Ali Hafid; Abd Radhi , Hussain (Diyala Journal of Medicine, 2019)
Background: Supracondylar fractures are usually seen in children, it is 10% of all pediatric fractures. The distal fragment may be displaced either posteriorly or anteriorly. Posterior (extension) type is the commonest type (95%) of cases suggests hyperextension injury. Aim: the aims of this study is to compare the results of conservative versus surgical treatment in severely displaced supracondylar fracture of humerus in children and to compare the results of posterior and lateral surgical approaches. Patients and Method: Forty six children with severely displaced posterior supracondylar fractures (Wilkins type IIB and III) were studied prospectively over 12 month's duration (Sep.2005-Sep.2006) in Al-Basra teaching hospital. Thirty five (76%) of patients were presented early (≤8 hrs.), while the other 11(24%) cases were received late (>8 hrs.). Closed reduction was done for all cases & it succeeded in 14(30%) cases only, while the other 32(70%) required open reduction through posterior approach mainly (23/32) and via lateral approach in the other (9/32). Crossed 2 K-wires, two lateral K-wires or Steinman pin through olecranon were the three modalities of fixations .Approach and way of fixation been selected according to surgeon preferences. Results: Among the complications recorded in this study joint stiffness lies on the top of the list, it affects 18 cases (39%) 16 cases treated surgically (12 by posterior approach and 4 by lateral approach)and 2 cases treated conservatively. The second common complication was malunion in the form of cubitus varus deformity which occur in 6 cases (13%) 4 treated conservatively and other 2 cases treated by posterior approach and fixation by Steinman pin through the olecranon process. In those treated by surgery complications were more in association with posterior approach. Conclusions: In ideal situations when fluoroscopy is available closed reduction and percutaneous fixation by multiple k-wires is good method of management. As the results and the rate of complications of early and late reduction are the same so there is no need for urgent reduction as long as there is no vascular compromise. The favorable approach was the lateral as it shows fewer complications in comparison with posterior one.